Paclobutrazol and ethylene on growth and nutrient accumulation in potted ornamental pineapple1 - Tellez, Hayver Olaya [UNESP] (2024)
With the decrease in residences, the demand for the production of plants with a landscape effect in reduced size and more compact has grown. The objective of this work was to evaluate the growth and accumulation of nutrients in a potted ornamental pineapple hybrid, treated with paclobutrazol and subjected to early floral induction. The experimental design used was a randomized block, factorial arrangement (2 × 5), with 4 replications and 4 plants per plot. The primary treatments were the presence and absence of the plant growth regulator paclobutrazol (PBZ). The secondary treatments were five times of floral induction with ethylene: 90, 120, 150, 180, and 210 days after transplanting (DAT) of the seedlings. At 130, 160, 190, 220, and 250 DAT, the following variables were evaluated: leaf area; fresh and dry mass of leaves; stems and roots; sodium; macro and micronutrient contents in the plant. The use of paclobutrazol reduces vegetative growth and the accumulation of fresh and dry mass of the aerial and root parts. The order of accumulation was K > N > Ca > Mg > P > S > Mn > Na > Fe > Zn > B > Cu, in plants not treated with PBZ, and K > N > Ca > Mg = P > S > Mn > Na > Fe > B > Zn > Cu, in plants treated with PBZ, showing that the use of paclobutrazol increases boron accumulation.